Positioning plant health within the evolving human-animal-environmental health paradigms - Maria Lodovica Gullino; Matias Pasquali; Massimo Pugliese; Ilaria Capua (One Health)
The evolution of the global scenario, which involves such converging crises as the climate crisis, the COVID-19 pandemic and its aftermath, and the Russia-Ukraine and Israel-Palestine wars, has underscored the fragility of the current food systems and the interdependence of human, animal, plant, and environmental health. Plant health is an important element in all these crises as plants provide food and feed, fix CO2, produce oxygen, and stabilize the soil. As a result of the Covid 19 pandemic, the One Health concept has finally obtained the attention of scientists and funding agencies. However, despite their role in global nutrition, the economy, and in climate crisis, plants are often excluded from the One Health efforts and funding streams. This paper advocates the need for an updated and more holistic view of plant health as public goods within the context of the evolving global challenges and explores opportunities within the Circular Health paradigm.